Conflict between Arabic and English in Nigeria Between tyranny and steadfastness Bachelma - Ibraheem, Lateef Onireti (Al-Adab Journal, 2015)
Before the advent of the British colonization, Arabic in Nigeria started as a language of trade and commerce. It later developed into the language of religion (Islam) and eventually metamorphosed into an official language in the Sokoto Caliphate and Ilorin Emirate of the country. The colonial strived to eradicate Islam and Arabic language with force and all sort of manipulations, but they met stiff opposition from the staunch adherents of the religion and the lovers of Arabic language. Eventually, English becomes the official Language of Nigeria and the more it strives to uproot the Arabic language, the more the later gets spread and developed. The conflict between the two languages continues up till today. The aim of this paper is to examine the factors that contributed to the survival of Arabic Language in Nigeria despite the oppression and challenges from English language, with emphasis on the impact of these factors on the growth and development of Arabic in Nigeria. The identified survival factors are positive contributions of individual Arabists who have passion for Arabic and Islam, establishment of formal Arabic Schools, receiving teachers from Arab countries, delegating students to Arab countries to study, philanthropic supports of the rich Muslims, establishment of Islamic organizations, establishment of Arabic Departments and Units in Nigerian tertiary institutions, advent of Arabic Typewriters, Computers and Printing Press, the internet facilities and others. The paper recommends that with necessary encouragement from the Nigerian and Arab countries Governments, Arabic will surely regain its enviable position in Nigeria.